2011
DOI: 10.1007/s00167-011-1732-5
|View full text |Cite
|
Sign up to set email alerts
|

Second-generation arthroscopic autologous chondrocyte implantation for the treatment of degenerative cartilage lesions

Abstract: Case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 51 publications
2
52
0
1
Order By: Relevance
“…Multiple studies have shown a positive effect, with increased function and pain reduction. 7,8,13,16,19,23 In clinical practice, subchondral BME is a frequent radiological observation in the postoperative course after ACI. In the present study we observed a high overall incidence of BME (78%) during the postoperative course of 3 years after third-generation ACI.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown a positive effect, with increased function and pain reduction. 7,8,13,16,19,23 In clinical practice, subchondral BME is a frequent radiological observation in the postoperative course after ACI. In the present study we observed a high overall incidence of BME (78%) during the postoperative course of 3 years after third-generation ACI.…”
Section: Discussionmentioning
confidence: 99%
“…2012). These scores were lower, however, and failures were observed more frequently than what had been reported previously in non-arthritic populations (Kon et al.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, subsequent studies developed different scaffolds composed of animal types I and III collagen, polyglycolic/polylactic acid, hyaluronic acid, fibrin gel and alginate to secure the cells within the lesion (i.e., matrix-assisted ACI, MACI; matrix-associated chondrocyte transplantation, MACT; and matrix-based ACI), as well as construction of engineered cartilage to achieve a more uniform repair of the lesion (Behrens et al, 2006;Beris et al, 2012;Filardo et al, 2012b;Pelissier et al, 2013;Rogers et al, 2010). The parameters and outcomes of mid-and long-term studies of patients treated with ACI, ACI seeded in scaff olds and other tissue-engineered cartilage techniques are listed in Table 1.…”
Section: Autologous Chondrocyte Transplantationmentioning
confidence: 99%